Mandibular Fracture in A 12‐Hour‐Old Neonate: Successful Conservative Management With Excellent Long‐Term Functional and Craniofacial Growth Outcomes - Symon Guthua; Wambeti Twahir; Krishan Sarna; Khushboo Sonigra; Jane Kabutu (Clinical Case Reports, 2026)
ABSTRACT Neonatal mandibular fractures are exceptionally rare but can be successfully managed with timely conservative treatment and anatomical reduction. Despite severe birth‐related maxillofacial trauma, the neonatal mandible demonstrates remarkable regenerative capacity, allowing excellent long‐term mandibular growth, occlusion, function, and facial aesthetics into adulthood.